PENGARUH MOTIVASI KERJA TERHADAP PRODUKTIFITAS KERJA PEGAWAI PADA KANTOR LURAH HARAPAN TANI - Eka Sri Wahyuni; Yaswar Aprilian; Sri Hidayanti (Indragiri Research Center (ingreat), 2026)
This study aims to determine the effect of work motivation on employee productivity at the Harapan Tani Village Office. This research uses a quantitative method with an associative approach. The population and sample in this study were all 20 employees using a saturated sampling technique. Data were collected through questionnaires, observation, and documentation, then analyzed using simple linear regression, t-test, and coefficient of determination (R²) with the help of SPSS. The results show that work motivation is in the high category with an average score of 4.14, while employee productivity is also in the high category with an average score of 4.18. The regression equation obtained is Y = 10.215 + 0.742X. The t-test results indicate that work motivation has a positive and significant effect on employee productivity (tcount 7.571 > ttable 2.101; sig 0.000 < 0.05). The coefficient of determination is 0.760, meaning that work motivation affects 76% of employee productivity, while the remaining 24% is influenced by other variables not included in this study. Thus, it can be concluded that the higher the work motivation, the higher the employee productivity.